Acute or Subacute, the Optimal Timing for Uncomplicated Type B Aortic Dissection: A Systematic Review and Meta-Analysis - Yang, Yang; Zhang, Xi-Hao; Chen, Zuo-Guan; Diao, Yong-Peng; Wu, Zhi-Yuan; Li, Yong-Jun (Frontiers in Surgery, 2022)
Objective: To evaluate the optimal timing of thoracic endovascular aortic repair (TEVAR) for acute and subacute uncomplicated B aortic dissection(uTBAD). Method: A comprehensive literature search was undertaken across three major databases (EMBASE/Medline, PubMed and Cochrane Library) and was assessed until November 2021 to identify studies reporting the outcomes of TEVAR utilized to treat patients with uTBAD. The continuous variables were compared between the two groups using t‐test and the categorical variables were compared using the χ2 test. Statistical analysis was performed using R software v.4.1. Result: Comprehensive literature search found 490 citations published within the predetermined time span of the analysis. Three studies including 1193 patients (acute group 718, subacute group 475) were finally included for downstream meta-analysis. Acute uTBAD group presented with higher rates both in 30-day complications (20.5% vs. 13.7%; P=0.014) and mortality (4.6% vs. 1.3%; P=0.004) than subacute group. Respiratory complications was significantly higher in the acute group than in the subacute group (10.8% vs. 5.0%; P=0.015). The procedure success rate (90.8% vs. 93.6%; P=0.329), the follow-up mortality (7.7% vs. 7.6%; P=1) and dissection related late mortality (3.9% vs. 5.3%; P=0.603) showed no significant difference. Conclusion: Our meta-analysis suggested that despite significantly higher 30-day complications and 30-day mortality in the acute uTBAD group, there was no significant difference in follow-up mortality between the two groups.